'Bio‐Load' and Bio‐Type Profiles of Mycobacterium avium subspecies paratuberculosis Infection in the Domestic Livestock Population Endemic for Johne's Disease: A Survey of 28 years (1985–2013) in India. (August 2014) - Singh, S. V.; Singh, P. K.; Singh, A. V.; Sohal, J. S.; Kumar, N.; Chaubey, K. K.; Gupta, S.; Rawat, K. D.; Kumar, A.; Bhatia, A. K.; Srivastav, A. K.; Dhama, K.
Summary: Bio‐load and bio‐profile of Mycobacterium avium subspecies paratuberculosis was studied in the domestic livestock population of the country. Of the 23 429 farm and farmer's animals screened, average bio‐load was 23.3% (Period of study; 28 years for goats; 13 years for sheep, cattle and buffaloes). Species‐wise, bio‐load was 20.1, 32.7, 39.3 and 28.3% in goats, sheep, cattle and buffaloes, respectively. Bio‐load was significantly lower in time period A ( P < 0.001) and B ( P < 0.03), compared with period C. Geographical zone‐wise, bio‐load of MAP was significantly higher ( P < 0.05) in Central zone compared with South, West, East and North zones. Bio‐load in 11 states ranged from 16.2 to 87.8%. Of 8450, 5643, 8185 and 1151 samples screened by microscopy, culture, indigenous ELISA and IS 900 blood PCR, 20.0, 10.6, 35.1 and 26.6% samples were positive, respectively. Bio‐load was 32.8 and 31.6% in farm and farmer's goats and sheep, respectively, and 62.1% in farmer's cattle. MAP bio‐load was also monitored in four farm units (three goats and one sheep) for breed improvement and three farm goats units for experimental purposes at Central Institute for Research on Goats in Mathura district. Of the 8025 goats and 1525 sheep that died from 1988 to 2013, 10.9 and 3.0% deaths were due to JD, respectively. On the basis of JD and suspected JD, 10.0 and 28.4% goats and 2.2 and 40.9% sheep, respectively were culled from the farm units in 25 years. Microscopic examination of 214 tissues (mesenteric lymph nodes and intestines) of 107 animals, it was observed that bio‐load of MAP was high (25.0–60.0%) in farm animals. 'Indian Bison Type' was the dominant biotype, irrespective of domestic livestock species and the geographical zone.